2018
DOI: 10.1124/mol.117.109603
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization and Tolerance of Mu Opioid Receptors on Pontine Kölliker-Fuse Neurons

Abstract: Acute desensitization of mu opioid receptors is thought to be an initial step in the development of tolerance to opioids. Given the resistance of the respiratory system to develop tolerance, desensitization of neurons in the Kölliker-Fuse (KF), a key area in the respiratory circuit, was examined. The activation of G protein-coupled inwardly rectifying potassium current was measured using whole-cell voltage-clamp recordings from KF and locus coeruleus (LC) neurons contained in acute rat brain slices. A saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
0
22
0
4
Order By: Relevance
“…However, we used repetitive daily methadone injections in the same rats from P0 to P5 and, in many other physiological systems, opioids induce tolerance within the first few exposures in rodents (Ling et al, 1989). Tolerance in the respiratory system has been observed after daily acute fentanyl (Laferrière et al, 2005), though this has not been observed in other studies (Emery et al, 2016;Levitt and Williams, 2018). Here, we found no evidence for tolerance after repeated daily acute methadone exposure, but we demonstrate the unique finding that opioid sensitivity is blunted acutely after MM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, we used repetitive daily methadone injections in the same rats from P0 to P5 and, in many other physiological systems, opioids induce tolerance within the first few exposures in rodents (Ling et al, 1989). Tolerance in the respiratory system has been observed after daily acute fentanyl (Laferrière et al, 2005), though this has not been observed in other studies (Emery et al, 2016;Levitt and Williams, 2018). Here, we found no evidence for tolerance after repeated daily acute methadone exposure, but we demonstrate the unique finding that opioid sensitivity is blunted acutely after MM.…”
Section: Discussionmentioning
confidence: 97%
“…Here, we found no evidence for tolerance after repeated daily acute methadone exposure, but we demonstrate the unique finding that opioid sensitivity is blunted acutely after MM. Furthermore, it is widely thought the respiratory control system does not develop opioid-induced tolerance ( Emery et al, 2016 ; Levitt and Williams, 2018 ), which increases vulnerability of patients to lethal respiratory frequency depression with opioid over-use. Thus, the demonstration of blunted opioid sensitivity represents a unique finding regarding sensitivity of developing neurorespiratory networks to opioids.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact variant of GABA‐B receptors in the KF is currently not known, acute KF slice experiments conducted in our laboratory provide functional evidence for the presence of GABA‐B receptors on KF neurons. Application of the GABA‐B agonist baclofen leads to the activation of G‐protein‐coupled inwardly rectifying K + (GIRK) conductance in a large population (~60%) of KF neurons in both rats and mice (Levitt, Abdala, Paton, Bissonnette, & Williams, 2015; Levitt & Williams, 2018; Varga, Reid, Kieffer, & Levitt, 2020). Furthermore, GABA‐B receptor positive neurons are also sensitive to opioids (Levitt & Williams, 2018; Varga et al., 2020).…”
Section: Gabamentioning
confidence: 99%
“…Application of the GABA-B agonist baclofen leads to the activation of G-protein-coupled inwardly rectifying K + (GIRK) conductance in a large population (~60%) of KF neurons in both rats and mice (Levitt, Abdala, Paton, Bissonnette, & Williams, 2015;Levitt & Williams, 2018;Varga, Reid, Kieffer, & Levitt, 2020). Furthermore, GABA-B receptor positive neurons are also sensitive to opioids (Levitt & Williams, 2018;Varga et al, 2020).…”
Section: Such Detailed Specific Description Of the Expression Of Gaba-bmentioning
confidence: 99%
“…In locus coeruleus, the decline in the peak outward current is about 50% during the application of a saturating concentration of an efficacious agonist. There are examples of neurons in which the decline in current is nearly complete (cholinergic striatal interneurons, personal observation) and other examples such as neurons in the Kolliker-Fuse in which there is little or no acute decline ( Levitt and Williams, 2018 ). Further, in the locus coeruleus, mechanisms of desensitization may change over time, as it has been observed that desensitization in older rats was homologous (occurring at MOR), whereas desensitization in younger rats appeared heterologous (affecting signaling through multiple receptors) ( Llorente et al, 2012 ).…”
Section: Cellular Tolerance and Acute Desensitization: Are They Separmentioning
confidence: 99%